The interplay of conformations and electronic properties in N-aryl phenothiazines. Issue 10 (24th March 2020) - Mayer, Laura; May, Lars; Müller, Thomas J. J.
Abstract : Extra and intra conformations govern electronic properties of N -aryl phenothiazines as shown by combined experimental and computational structure–property relationships. Abstract : A broad series of electronically diverse N -aryl substituted phenothiazines was readily synthesized by Buchwald–Hartwig amination of 10 H -phenothiazine and aryl bromides with variable electronic nature in moderate to excellent yields (61–97%). This library of N -aryl phenothiazines was studied with respect to their electronic properties by absorption and emission spectroscopy, cyclic voltammetry, and quantum chemical calculations to elucidate the electronic structure. Furthermore, DFT calculations allow assigning substituent dependent dominance of intra or extra conformations by virtue of the electronic nature of the remote N -aryl substituent. Electron releasing substituents favor intra and electron withdrawing substituents favor extra conformations in the electronic ground state. The experimentally determined oxidation potentials as well as the calculated molecular geometries strongly correlate with Hammett σ p parameters of the remote para -substituents. Therefore, transmission of the substituent effect operates by both resonance and inductive mechanisms. This linear correlation equation can be applied to assign new sigma parameters σ p for several substituents on the basis of the experimentally determined oxidation potentials.